Hiter algoritem za poenostavljanje in obnovitev trikotniških mrež za prenos rezultatov MKE preko svetovnega spleta - Krivograd, Sebastian (Strojniški vestnik, 2003)
This paper describes a fast algorithm for the decimation of triangular meshes,illustrated by transferring the results of a finite-element method (FEM) analysis. The obtained meshes preserve all the key characteristics of the original meshes with considerable less data, which makes the algorithm very useful for data exchange over the web. First, the FEM is briefly described as an approximate and numerical method that mostly results in an excessive quantity of data. A brief overview of the possible approaches to data reduction for triangular meshes is given, and the solution with node elimination is presented. To speed up the search for the nodes to be removed, a hash table is applied, organized heuristically and suitable for engineering data. Finally, the paper presents an analysis of a time-and-space complexity analysis and a practical example with a reduction of FEM data results, enabling efficient transfer over the web. The practical results obtained during the testing of the FEM results transfer confirm the theoretical estimation of linear time complexity.
Keywords: geometrija računalniška; poenostavljanje mrež; metode končnih elementov; svetovni splet; trikotniške mreže; algoritmi